HUBUNGAN INTENSITAS NYERI PUNGGUNG BAWAH UNILATERAL DENGAN DERAJAT OSTEOARTRITIS DAN INTENSITAS NYERI LUTUT KONTRALATERAL DI RUMAH SAKIT UMUM DAERAH DR. ZAINOEL ABIDIN BANDA ACEH - Riska Santi Putri; Dessy Rakhmawati Emril; Syamsul Rizal; Nova Dian Lestari; Yopie Afriandi Habibie (Jurnal Sinaps, 2022)
Introduction: Low back pain (LBP) is one of the most common forms of musculoskeletal pain and is often encountered in everyday life. LBP can interfere with a person's work performance so that it can reduce human productivity. The pain caused by LBP can radiate to the ipsilateral leg and cause the contralateral leg to withstaand more weight due to the inability of the ipsilateral leg. This condition can also cause osteoarthritis (OA) in the contralateral leg of patients with LBP. Aims: This study aims to analyze the relationship between unilateral lower back pain and the degree of contralteral knee osteoarthritis at Dr. Zainoel Abidin Banda Aceh. Methods: This study was an observational analytic study with a cross-sectional design. The sample in this study was taken using the total sampling method. Based on the inclusion and exclusion criteria, 17 people can be analyzed. Data collection was carried out by collecting medical records in neurological clinics and radiology installations.Results: The results of this study indicate that 50% of respondents showed a degree of pain on a scale of 5 (moderate category), 40% of respondents indicated the degree of knee OA grade 2 and grade 3. Based on the results of the analysis with the Spearman test, it was found that there was a relationship between unilateral low back pain intensity and the degree OA of the contralateral knee (p value = 0.026) and based on the results of the analysis with the Spearman test, it was also found that there was a relationship between the intensity of unilateral low back pain and the intensity of contralateral knee pain (p value = 0.047). Discussion: The conclusion of this study is that there is a relationship between unilateral low back pain with the degree of osteoarthritis and the intensity of contralteral knee pain in Dr. General Hospital. Zainoel Abidin Banda Aceh.